Effect of absorbed dose on post-irradiation coloration and interpretation of polymerization reaction in the Gafchromic EBT3 film. (October 2021) - Sharma, Megha; Singh, Ranjit; Dutt, Sunil; Tomar, Parsee; Trivedi, Gaurav; Robert, N.
Abstract: The change in the optical density/transmittance obtained for dose delivered to EBT3 films by 15 MeV photon beam in the range 0.1–20 Gy as a function of the time elapsed between film irradiation and readout is analyzed. The polymerization chain reaction expected for monomer unit i.e., di-acetylene, in EBT3 film is predicted. These films are repeatedly scanned up to 104 h after irradiation by EPSON expression 11000XL flatbed scanner and analyzed by ImageJ software. At doses, ≤ 1 Gy, the average change in net transmittance over 104 hours, is 19.6% and for dose range between 1.5 Gy-7 Gy and 8 Gy–20 Gy, the values are 5.7% and 2.7%, respectively. During initial 24 hours, the increase in net transmittance for dose range 0.1 Gy–1 Gy, 1.5 Gy–5 Gy and 6 Gy–20 Gy are 0.5%–29.6% (mean 14.2%), 2.4%–6.8% (mean 3.6%) and 1.5% - 3.3% (mean 2.3%), respectively. The di-acetylene monomer in Gafchromic film undergoes addition at 1, 4 positions and polymerization reaction involves three different steps i.e., chain initiation, propagation and termination. At low absorbed doses i.e., ≤1 Gy, the chain termination step is prolonged and post-irradiation changes have attained a saturated value (plateau region within ±2%) for a considerably longer period (average 24 h) as compared to the film irradiated with higher doses. The Optical density (OD)/transmittance increases with elapsed time while its rate of change decreases with time and saturation in OD is a dose-dependent phenomenon. At high absorbed doses, the changes due to post-irradiation coloration will be least significant as the RCF saturates rapidly i.e. within 6 hours. It is necessary to scan EBT3 film after 24 h and 6 h of irradiation for doses ≤1 Gy and above 1 Gy, respectively. Highlights: Di-acetylene monomer in irradiated EBT3 Gafchromic film undergoes polymerization. Length of polymer chain decreases with increase in absorbed dose. Post-irradiation changes behave differently for low and high dose range. Saturation in Post irradiation coloration is comparatively longer for low doses. In high doses, post irradiation changes saturates rapidly within 6 h of irradiation.